2013
DOI: 10.2485/jhtb.22.337
|View full text |Cite
|
Sign up to set email alerts
|

Bone Augmentation Using Novel Unidirectional Porous Hydroxyapatite with Bone Morphogenetic Protein-2 on Rat Skull

Abstract: Unidirectional porous hydroxyapatite (UDPHAp) is a material whose microstructure consists of crosssectional oval pores with a pore diameter in the range of 100-300 m that penetrate through the material. UDPHAp has proven suitable for osteogenesis and angiogenesis. The present study was designed to evaluate the osteogenic effect of a newly developed UDPHAp as a carrier of recombinant human bone morphogenetic protein-2 (rhBMP-2) in a rat onlay graft model. UDPHAp was implanted beneath the calvarial periosteum of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
(16 reference statements)
0
3
0
Order By: Relevance
“…Other investigators have reported that a scaffold made of HAp with a unidirectional porous structure was more useful than a spherical interconnected porous structure since it could be impregnated with more cells [ 32 ]. When recombinant human bone morphogenetic protein-2 was implanted in bony defects of the skull in mice, significantly more new bone formation was observed than when HAp with a spherical interconnected porous structure was used [ 33 ]. Finally, thermal stimulation was found to promote new bone formation in the blocks implanted in rat tibia [ 34 ].…”
Section: Animal Experiments For the Development Of Regenos ® ; Unidirectional Porous Hapmentioning
confidence: 99%
“…Other investigators have reported that a scaffold made of HAp with a unidirectional porous structure was more useful than a spherical interconnected porous structure since it could be impregnated with more cells [ 32 ]. When recombinant human bone morphogenetic protein-2 was implanted in bony defects of the skull in mice, significantly more new bone formation was observed than when HAp with a spherical interconnected porous structure was used [ 33 ]. Finally, thermal stimulation was found to promote new bone formation in the blocks implanted in rat tibia [ 34 ].…”
Section: Animal Experiments For the Development Of Regenos ® ; Unidirectional Porous Hapmentioning
confidence: 99%
“…After checking the expression of NC marker as previously described 12) , iPS-NCLCs were cultured and maintained in DMEM containing 10% FBS and 50 U/ml and 50 µg/ml PenicillinStreptomycin on CorningTM PrimariaTM tissue culture dishes (Thermo Fisher Scientifi c) to induce MSCs. For iPS-NCLC-MSCs cultured on hydroxyapatite (HA), unidirectional porous HA scaffolds [18][19][20] (Kurarife, Kuraray Medical Inc., Tokyo, Japan) were coated with fi bronectin overnight at 4°C and washed with PBS 3 times. Dissociated iPS-NCLC-MSCs were seeded on the HA scaff olds and cultured in DMEM supplemented with 10% FBS for 2 days before osteoinduction.…”
Section: Cell Culture and Msc Inductionmentioning
confidence: 99%
“…Bioceramics can be prepared with the same chemical composition similar to that of the human bone [1,2] . Bioceramics are commonly used in the medical fields as dental and bone implants because they have the ability to form a direct bond with the living bone in the presence of human physiological environment and because they have the potency to produce biomimetic hydroxyapatite apatite layer on the bone surface [3] .…”
Section: Introductionmentioning
confidence: 99%